Environment and Growth - Ryo Horii; Masako Ikefuji (Fondazione Eni Enrico Mattei (FEEM), 2014)
This paper examines the implications of the mutual causality between environmental quality and economic growth. While economic growth deteriorates the environment through increasing amounts of pollution, the deteriorated environment in turn limits the possibility of further economic growth. In a less developed country, this link, which we call limits to growth, emerges as the poverty-environment trap, which explains the persistent international inequality both in terms of income and environment. This link also threatens the sustainability of the worlds economic growth, particularly when the emission of greenhouse gases raises the risk of natural disasters. Stronger environmental policies are required to overcome this link. While there is a trade-off between the environment and growth in the short run, we show that an appropriate policy can improve both in the long run.
Keywords: Q5; 330; Environmental Kuznets Curve; Limits to Growth; Poverty-Environment Trap; Sustainability; Natural Disasters